ANALISIS KOLABORASI AKTOR PENTAHELIX DALAM PENGEMBANGAN EKONOMI KREATIF UMKM DI PUSAT KULINER PANCASILA KOTA PALOPO - Samsuri Samsuri; Waldi Waldi; Nurfaisah Nurfaisah; Rifqiansyah Rifqiansyah (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study examines the importance of Pentahelix actor synergy in developing a creative economy based on micro, small, and medium enterprises at the Pancasila Culinary Center in Palopo City. The issue addressed in this study arises from the significant potential of the culinary area as a local economic space, while it still faces challenges related to coordination, business capacity improvement, promotional strengthening, and sustainable mentoring. This study aims to analyze the roles of academics, business actors, communities, government, and media in supporting creative economy development, as well as to identify forms of collaboration, supporting factors, and inhibiting factors that influence the effectiveness of inter-actor synergy. This research employed a descriptive qualitative approach through observation, interviews, documentation, and literature review. The findings show that each actor has performed roles according to their respective capacities: the government acts as a facilitator, business actors serve as economic drivers, communities strengthen networks, academics provide knowledge-based assistance, and media support publication and promotion. Collaboration has been reflected in training, exhibitions, mentoring, promotion, and publication. However, it has not been fully optimized due to the absence of institutionalized coordination, unequal digital capabilities among business actors, and inconsistent program evaluation.